Poetry and islands : materiality and the creative imagination - Patke, Rajeev S. (Rajeev Shridhar) (Rethinking the island., 2018)
"This book demonstrates the variety of ways in which the materiality of islands is intertwined in a symbiotic relationship with the capacity of the imagination to make islands the site and embodiment of a host of recurrent human desires, anxieties, and hopes"--